Methodology for Identifying the Boundaries of Agglomerations based on Statistical Data - Tolmachev, Dmitry E.; Kuznetsov, Pavel D.; Ermak, Sergey V. (Economy of Regions, 2021)
Significant difference in development between the municipalities is an obstacle for achieving economic sustainability in many Russian regions. Regional development strategies and plans of various municipalities often cannot be synchronised because of their incompatibility. Moreover, municipalities usually lack necessary resources to implement their strategies. To solve these problems, we identified groups of municipalities (key units of the settlement system (KUSS)) based on the existing socio-economic relations, common challenges and development potential. We propose a methodology for identifying KUSS and describe its application. This methodology relies on statistical data available at the municipal level. To assess the interconnection of municipalities, we used 6 statistical socio-economic indicators and 1 integrated index of Gross Municipal Product (GMP). The difference in the first 6 indicators of the development of municipalities demonstrated, that less developed municipalities tend to more developed ones. We used the values of gross municipal product to define high mutual attraction of large municipalities (similar to the gravity model). The distance between municipalities reduced their mutual influence. Due to the limited data set, it was necessary to consider the reliability of the identified inter-municipal relations. Thus, we compared the obtained results with empirical data on population distribution and circular migration between municipalities in the region. The comparison of our calculations and actual data showed high precision of the presented methodology. The resulting grouping of municipalities allowed identifying 21 key units of the settlement system in Sverdlovsk oblast. The proposed methodology can be usedfor determining large groups of municipalities in Sverdlovsk oblast, as well as in other Russian regions.